Impact resistance of sustainable construction material using light weight oil palm shells reinforced geogrid concrete slab - Muda Z.C.; Malik G.; Usman F.; Beddu S.; Alam M.A.; Mustapha K.N.; Birima A.H.; Zarroq O.S.; Sidek L.M.; Rashid M.A. (Institute of Physics Publishing, 2023)
This paper investigate the performance of lightweight oil palm shells (OPS) concrete slab with geogrid reinforcement of 300mm 300mm size with 20mm, 30mm and 40 mm thick casted with different geogrid orientation and boundary conditions subjected to low impact projectile test. A self-fabricated drop-weight impact test rig with a steel ball weight of 1.2 kg drop at 1 m height has been used in this research work. The main variables for the study is to find the relationship of the impact resistance the slab thickness, boundary conditions and geogrid reinforcement orientation. Test results indicate that the used of the geogrid reinforcement increased the impact resistance under service (first) limit crack up to 5.9 times and at ultimate limit crack up to 20.1 times against the control sample (without geogrid). A good linear relationship has been established between first and ultimate crack resistance against the slab thickness. The orientation of the geogrid has minor significant to the crack resistance of the OPS concrete slab. OPS geogrid reinforced slab has a good crack resistance properties that can be utilized as a sustainable impact resistance construction materials. Published under licence by IOP Publishing Ltd.